2015
DOI: 10.1002/ejoc.201500912
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Synthesis of 2,5‐Epoxybenzo[f][1,4]oxazepines by Tandem Reaction of 1‐Sulfonyl‐1,2,3‐triazoles and Salicylaldehydes

Abstract: Readily available 1‐sulfonyl‐1,2,3‐triazoles were converted into α‐imino carbenes in the presence of catalytic amounts of rhodium(II) salts. The carbenes underwent a tandem reaction with salicylaldehydes to provide a series of functionalized 2,5‐epoxybenzo[f][1,4]oxazepines in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…1,2,3-Triazoles 1a – d , k , 1e , 1f , 1g , 1h , and 1i , j and diazo compounds 17a , c are known compounds, which were prepared by the reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…1,2,3-Triazoles 1a – d , k , 1e , 1f , 1g , 1h , and 1i , j and diazo compounds 17a , c are known compounds, which were prepared by the reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Control experiment by using chiral benzyl alcohol produced the α- ). [44] The reaction scope was demonstrated by varying valuable functional groups on both the substrates and found that electronic variation had minimal impact on the reaction efficiency. Additionally, o-hydroxyacetophenone was also converted to the corresponding 1,4-oxazepine in good yield.…”
Section: Oà H Nà H Insertionmentioning
confidence: 99%
“…(Scheme 27). [40] The reaction scope was broad, asv arious triazoles and salicylaldehyde derivatives could participate in the reaction. Twop ossible mechanisms were proposed.…”
Section: Attack By Oxygen Atommentioning
confidence: 99%
“…In 2015, Li and co‐workers reported a unusual transformation whereby salicylaldehyde derivatives could also react with the N ‐sulfonyl‐1,2,3‐triazoles 1 to give heterocycles. (Scheme ) . The reaction scope was broad, as various triazoles and salicylaldehyde derivatives could participate in the reaction.…”
Section: Reactions Of N‐sulfonyl‐123‐triazolesmentioning
confidence: 99%